The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.ijgo.2015.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Prospective cohort study of persistent hypertension following pre-eclampsia at Medani Hospital, Sudan

Abstract: Persistent hypertension 6weeks after delivery was common among patients who experienced pre-eclampsia in Sudan (particularly severe pre-eclampsia) regardless of patients' age and parity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…This study observed high rates of persistent hypertension regardless of HDP subtype (21% and 61% of women with gestational hypertension and pre-eclampsia, respectively). This is in line with findings from other studies within sub-Sahara Africa in Nigeria, Cameroon, Uganda and Sudan [ 10 11 12 13 14 ], which reported rates between 25.5% and 35.6% six weeks to six months after delivery of HDPs-complicated pregnancies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study observed high rates of persistent hypertension regardless of HDP subtype (21% and 61% of women with gestational hypertension and pre-eclampsia, respectively). This is in line with findings from other studies within sub-Sahara Africa in Nigeria, Cameroon, Uganda and Sudan [ 10 11 12 13 14 ], which reported rates between 25.5% and 35.6% six weeks to six months after delivery of HDPs-complicated pregnancies.…”
Section: Discussionsupporting
confidence: 92%
“…This retention rate was also commendable based on recommended follow up rates between 50 – 80% for cohort studies [ 15 16 17 ]. To our knowledge, this is the largest cohort of women with HDPs followed up the longest in African settings (previous single-center studies in Cameroon, Nigeria, Sudan and Ugandan were for between six weeks to six months) [ 10 11 12 13 14 ]. This study enrolled women from eight tertiary health facilities spread across Nigeria ensuring diversity of patients and settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, none of the biochemical (creatinine /uric acid/aspartate aminotransferase/alanine aminotransferase levels) or demographic (age, pregnancy duration, parity, and BMI) variables studied showed an association with persistent hypertension post preeclampsia. A study by Fadalallah et al [17] in Sudan demonstrated similar findings of non-association. This appears differently in relation to past studies that showed various predictive variables (age, pregnancy duration, age, creatinine, and severe preeclampsia/early onset preeclampsia) for the persistent hypertension post-preeclampsia [12][13][14][15].…”
Section: Discussionsupporting
confidence: 53%
“…Preeclampsia/eclampsia is the leading cause of obstetric complications and maternal mortality in Sudan [1518]. The current study was conducted at Omdurman Maternity Hospital, Sudan to determine the level of AMH in women with preeclampsia and to add on our recent research on preeclampsia in Sudan [1921]. …”
Section: Introductionmentioning
confidence: 99%